Formulation and in-vitro anticancer activity of nilotinib immediate release and ibrutinib sustained release pellets - Gupta, Vishal; Gupta, Jitendra (Journal of Applied Pharmaceutical Research, 2024)
Background: Blood cancer is a significant contributor to mortality rates worldwide, and its prevalence is projected to rise on a global scale. This trend places considerable strain on healthcare systems and necessitates the expedited development of innovative treatments by pharmaceutical firms to remain competitive. Conventional pellets produce rapid plasma drug levels, but they might cause side effects, decrease effectiveness, and lead to poor therapeutic management. Ibrutinib and Nilotinib are employed to treat leukemia patients. Methodology: The current research aims to formulate, characterize, and anticancer effect of Nilotinib immediate release (NIR) and Ibrutinib sustained release (ISR) seal sugar-coated pellets. Micrometric properties estimated the characterization of the drug pellets, and surface morphology was estimated using scanning electron microscopy. Drug excipient compatibility studies, stability studies, and in-vitro drug release were accessed. Result & Discussion: The results of pellet formulations FNI-1 to FNI-5 showed that FNI-5 formulations showed 100±6.0 µm size and possessed excellent mechanical strength for giving pellets a good self-life; also, due to the higher drug content up to 99%, FNI-5 was the best suited for pellet formulation and because NIR showed 99.18 ± 2.12 drug release at 2h and ISR 99.03±3.74% up to 12h so that anticancer concentration maintained for prolonged period. The standard dose for cytotoxicity against the THP-1 cell line of Nilotinib was found to be 200 mg, and the maintenance oral dose of Ibrutinib was 140mg, with four times the intake of the drug up to 560 mg.  In an in vitro study in FNI-5 (final formulation), the dose of Ibrutinib was reduced to 420 mg. Conclusion: A synergistic effect of Ibrutinib and nilotinib drugs was observed in the inhibition of cancer cell growth, with an IC50 value of 4.585 µg/mL